Evaluation of tissue Doppler echocardiography in the assessment of ventricular function in asthmatic children - Amal G Mohamed; Sally R Eid; Nada M F. ElSayed; Safaa A Mohammed (Journal of Medicine in Scientific Research, 2021)
Background Bronchial asthma is one of the commonest diseases in children. It not only affects the lung but also other organs, including the heart. Our study aims to assess the effect of bronchial asthma with varying degrees of severity on the ventricular function of the heart using tissue Doppler imaging. Patients and methods This is a case–control study that was performed at the Pediatric Department of Al-Azhar University Hospital and included 50 patients with bronchial asthma, who were compared with 50 age-matched and sex-matched healthy children as a control group. All children were subjected to full history taking, complete physical examination, measurement of pulmonary function, and echocardiography by conventional and tissue Doppler. Results Echocardiographic parameters in asthmatic children were nearly similar to those of healthy children. Subgroup analysis showed no significant differences between controlled and uncontrolled asthmatics except for the tricuspid lateral E' velocity, which was lower in uncontrolled asthmatics when compared with the controlled. There were statistically significant differences among mild, moderate, severe asthmatic groups regarding pulmonary function tests, which were lower in severe asthmatic patients when compared with mild asthmatic patients. Conclusions Although there was no statistically significant difference between asthmatic patients and controls, we noticed that the right ventricular tissue Doppler indices were lower in asthmatic patients than controls, which should be considered, and a statistically significant relation between tissue Doppler echocardiography and the result of the pulmonary function tests. So, the disease severity can be predicted using tissue Doppler echocardiography.